Unraveling Urban Mobility Nodes: The Role of BRT Trans Semarang Feeders in Public Transportation Transformation - Muhammad Nuqlir Bariklana,; Muhajarah, Kurnia (Jurnal Governansi, 2025)
The rapid growth of private vehicles in Semarang has not been matched by road capacity, leading to chronic congestion and declining urban environmental quality. In response, the city government introduced the Trans Semarang Bus Rapid Transit (BRT) system, complemented by feeder services since 2019 to address first mile–last mile challenges. This article aims to analyze the effectiveness of the Trans Semarang feeder in expanding accessibility, enhancing system integration, and reducing dependence on private vehicles. A descriptive qualitative approach was employed, combining in-depth interviews, participant observation, and document analysis, framed by Van Meter and Van Horn’s implementation theory and the concept of sustainable urban mobility. The findings show that feeders play a crucial role in connecting residential areas inaccessible to regular buses. However, their effectiveness is constrained by suboptimal stop locations, irregular headways, limited transit facilities, and weak integration of ticketing and information systems. The analysis highlights that feeder success depends heavily on supporting ecosystems: pedestrian access quality, service reliability, and reduced transfer penalties. Policy implications include improving micro-infrastructure, strengthening operational management, integrating fares and information systems, enhancing public communication, and diversifying funding sources. This study concludes that the Trans Semarang feeder has the potential to become a model for inclusive public transport in medium-sized Indonesian cities, provided that consistent and sustained integration strategies are implemented.